Double-vacancy ZnCdS solid solution photocatalyst as well as preparation method and application thereof
By constructing a ZnCdS solid solution through low-temperature water bath synthesis and NaOH ultrasonic treatment, the surface defects were solved, thus addressing the photocorrosion problem of ZnxCd1-xS photocatalysts. This resulted in highly efficient and stable photocatalytic hydrogen production performance, significantly improving hydrogen production efficiency.
Patent Information
- Application Number
- CN202610203436.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-12
- Publication Date
- 2026-03-20
- Estimated Expiration
- 2046-02-12
AI Technical Summary
Existing ZnxCd1-xS photocatalysts are consumed by electrons before photogenerated holes are transferred to the surface, leading to photocorrosion and decreased photocatalytic activity. Furthermore, existing methods for constructing surface defects are complex, costly, or energy-intensive, making it difficult to achieve efficient hydrogen production.
ZnCdS solid solution was synthesized in a low-temperature water bath using a specific ratio of cadmium, zinc and sulfur sources. An alkaline reducing environment was established using NaOH and double vacancies were constructed by ultrasonic treatment to form stable surface defects that serve as electron and hole trapping sites.
It achieves a high efficiency improvement in hydrogen production performance, requires no additional catalyst, has a hydrogen production efficiency of up to 12.69 mmol·g-1·h-1, good repeatability, low cost, and simple procedure.
Smart Images

Figure CN121695891A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of photocatalyst preparation, and particularly relates to a double-vacancy ZnCdS solid solution photocatalyst and a preparation method and application thereof. BACKGROUND
[0002] Due to the gradual depletion of fossil fuels, global industrialization and rapid consumption of natural resources, environmental problems and energy crises seriously threaten the sustainable development of today's society. At present, the solution to the energy crisis still relies heavily on conventional fossil fuels, which has increasingly aggravated environmental pollution. Hydrogen energy, as a clean energy, has no toxic and harmful combustion products and is regarded as a key direction to achieve sustainable energy development.
[0003] Since Fujishima et al. discovered that TiO2 can produce hydrogen under ultraviolet light, photocatalysis research has rapidly developed. Among numerous photocatalysts, metal sulfides stand out in photocatalytic hydrogen production. In particular, Zn x Cd 1-x S, as a ternary metal sulfide solid solution, has the advantages of both narrow-band-gap CdS (2.4 eV) and wide-band-gap ZnS (3.6 eV). However, it was found in experiments that photo-generated holes would be transferred to the surface of Zn x Cd 1-x S before being consumed by an electron donor, in which case, the sulfur ions would be oxidized to sulfur or sulfate, resulting in severe photo-corrosion of Zn x Cd 1-x S and limiting its photocatalytic activity.
[0004] Surface defect engineering of photocatalysts can lead to higher absorption of visible light, form new catalytically active sites to extend the lifetime of electrons and holes, and thus dynamically improve the photocatalytic performance of photocatalysts. In summary of existing research, current surface defect engineering is mainly constructed by hydrothermal / solvothermal method, chemical reduction method, high-temperature calcination method, etc. However, these methods are relatively complex in terms of procedures and conditions control. The hydrothermal / solvothermal method has high equipment cost and safety risk, the chemical reduction method has strong reagent dependence and the product is easily contaminated, and the high-temperature calcination method has huge energy consumption and is easy to cause structural changes. Moreover, in some research, Zn x Cd 1-x S solid solution constructed by surface defect engineering also needs additional cocatalysts to achieve ideal hydrogen production effect. Therefore, it is of great significance to further study a simpler method to break through the hydrogen production limit of Zn x Cd 1-x S and improve the hydrogen production stability of Zn x Cd 1-x S solid solution. SUMMARY
[0005] The technical problems to be solved by the present application are to overcome the shortcomings of the prior art, and to provide a double-vacancy ZnCdS solid solution photocatalyst with high hydrogen production rate, good repeatability, simple preparation, low cost and an application thereof.
[0006] To solve the above technical problems, the present application adopts the following technical solutions.
[0007] A preparation method of a double-vacancy ZnCdS solid solution photocatalyst comprises the following steps: (1) A cadmium source, a zinc source and a sulfur source are added to anhydrous ethanol for stirring and dissolving, the mass ratio of the cadmium source, the zinc source and the sulfur source is 1:9:3, the mass-volume ratio of the zinc source to the anhydrous ethanol is 0.45 g-0.54 g: 50 mL-60 mL, and the reaction is carried out under the condition of a water bath at 70-90 DEG C. After the reaction, the powder-like ZnCdS solid solution is obtained through suction filtration, washing and drying, and the powder-like ZnCdS solid solution is specifically powder-like ZnCdS solid solution. 0.9 Cd 0.1 S solid solution; (2) NaOH is added to water for stirring and dissolving, the mass-volume ratio of the NaOH to the water is 0.8 g-0.9 g: 60 mL-65 mL, the NaOH solution is obtained, then the powder-like ZnCdS solid solution obtained in step (1) is added, the mass ratio of the NaOH to the powder-like ZnCdS solid solution is controlled to be 1:0.1-0.2, and then ultrasonic treatment is carried out, the ultrasonic frequency is 35 kHz-40 kHz, and the ultrasonic time is 30 min-60 min. After the ultrasonic treatment, the double-vacancy ZnCdS solid solution photocatalyst is obtained through suction filtration, washing and drying.
[0008] In the above preparation method of the double-vacancy ZnCdS solid solution photocatalyst, preferably, in step (1), the cadmium source is cadmium acetate dihydrate, the zinc source is zinc acetate dihydrate, and the sulfur source is thioacetamide.
[0009] In the above preparation method of the double-vacancy ZnCdS solid solution photocatalyst, preferably, in step (1), the proportions of the cadmium source, the zinc source, the sulfur source and the anhydrous ethanol are 0.06 g: 0.54 g: 0.18 g: 60 mL.
[0010] In the above preparation method of the double-vacancy ZnCdS solid solution photocatalyst, preferably, in step (2), the mass-volume ratio of the NaOH to the water is 0.8 g: 60 mL, the ultrasonic frequency is 40 kHz, and the ultrasonic time is 45 min.
[0011] In the above preparation method of the double-vacancy ZnCdS solid solution photocatalyst, preferably, in step (1), the stirring and dissolving time is 10 min-15 min, and the reaction time is 1 h-2 h.
[0012] Preferably, in the step (2), the stirring and dissolving time is 10-15 minutes.
[0013] Preferably, in the step (1), the obtained solid is dried after repeated filtration and washing for 3-6 times, and the drying temperature is 60-65 DEG C and the drying time is 12-14 hours.
[0014] Preferably, in the step (2), the obtained solid is dried after repeated filtration and washing for 3-6 times, and the drying temperature is 60-65 DEG C and the drying time is 12-14 hours.
[0015] As a general technical concept, the application further provides a double vacancy ZnCdS solid solution photocatalyst prepared by the above-mentioned preparation method of double vacancy ZnCdS solid solution photocatalyst.
[0016] As a general technical concept, the application further provides an application of the above-mentioned double vacancy ZnCdS solid solution photocatalyst in the field of photocatalytic hydrogen production.
[0017] In the application, ZnCdS can also be written as Zn x Cd 1-x S.
[0018] The main innovation of the application is that: (1) the mass ratio of cadmium source, zinc source and sulfur source for preparing ZnCdS solid solution (Zn x Cd 1-x S solid solution) is 1:9:3, the mass-volume ratio of zinc source and anhydrous ethanol is 0.45-0.54 g:50-60 mL, and the powder-like Zn 0.9 Cd 0.1 S solid solution is obtained, the photocatalytic hydrogen evolution rate reaches the maximum value when x=0.9, and is much higher than the photocatalytic hydrogen evolution performance when x=0.3, 0.5, 0.7 and 1, the double vacancy ZnCdS solid solution photocatalyst prepared when x=0.9 has several times higher photocatalytic hydrogen evolution performance than the photocatalytic hydrogen evolution performance of the photocatalyst prepared when x takes other values, and the highest hydrogen production efficiency is achieved, which shows that the photocatalytic hydrogen evolution performance has a huge improvement space through component optimization.
[0019] (2) In this invention, powdered ZnCdS solid solution was synthesized entirely in a low-temperature water bath environment of 70℃~90℃. The applicant found that under these conditions, the crystal nucleation and growth rate is slower, which is conducive to the uniform incorporation of defects (such as sulfur vacancies) into the crystal lattice rather than their concentrated formation on the surface. This facilitates the control of defect formation and avoids uneven defect distribution or the generation of unnecessary impurity phases due to excessively rapid reaction. Consequently, a considerable and stable vacancy-forming structure was obtained, which is a prerequisite for achieving dual vacancies. In addition, the 70℃~90℃ water bath reaction is milder and more controllable than the high-temperature hydrothermal method (usually >150℃) of the prior art.
[0020] (3) In this invention, after synthesizing powdered ZnCdS solid solution, double vacancies are constructed. NaOH is added to establish a stable reducing environment with relatively low formation energy. The specific alkaline environment can stimulate the overflow of Zn and S atoms. Then, ultrasonic treatment at a specific time and frequency can effectively accelerate and consolidate the formation of double vacancies.
[0021] Compared with the prior art, the advantages of the present invention are as follows: 1. The preparation method of this invention uses a specific ratio of cadmium, zinc, and sulfur sources to prepare powdered ZnCdS solid solution under low-temperature water bath conditions of 70℃~90℃ throughout the entire process. The reaction time is only 1-2 hours. After synthesizing the ZnCdS solid solution, an alkaline reducing environment is established using NaOH, which enables the successful construction of surface defects in the ZnCdS solid solution. Simultaneously, ultrasound is used to further accelerate and consolidate the formation of surface defects. The dual-vacancy ZnCdS solid solution photocatalyst prepared by this invention is regulated by sulfur and zinc surface defects. The sulfur and zinc surface defects on the dual-vacancy ZnCdS solid solution photocatalyst act as electron and hole trapping sites, respectively, which not only prolongs the lifetime of holes and electrons but also greatly improves the separation efficiency of electrons and holes. The positively charged state is conducive to providing free charge carriers to the conduction band of the sulfide photocatalyst. At the same time, metal vacancies can induce a negatively charged state, which is conducive to the valence band accepting free holes. The captured photogenerated electrons are used for photocatalytic hydrogen production, and the holes are used for sacrificial agent consumption, which helps to reduce electron-hole pair recombination. The combination of the two synergistically promotes photocatalytic hydrogen production.
[0022] The preparation method of the present invention can achieve a high efficiency improvement in hydrogen production performance without loading any other photocatalysts or co-catalysts. The method does not use any complex reducing agents for defect construction, and induces and consolidates the formation of double vacancies by using NaOH and ultrasonic treatment under specific conditions at room temperature.
[0023] In summary, the preparation method of the present invention has a simpler procedure, shorter preparation time, better hydrogen production effect, higher repeatability and stability, and the raw materials are readily available, with low cost and low energy consumption.
[0024] 2. The double-vacancy ZnCdS solid solution photocatalyst prepared in this invention (i.e., defective V-Zn) x Cd 1-x S) can be applied to the field of photocatalytic hydrogen production, achieving a hydrogen production efficiency of up to 12.69 mmol·g in 10 vol% triethanolamine (TEOA) without any co-catalyst. -1 ·h -1 It is 23.94 times that of pure ZnS and 11.64 times that of pure CdS. Attached Figure Description
[0025] Figure 1 The image shows a SEM image of the dual-vacancy ZnCdS solid solution photocatalyst prepared in Example 1. In the image, EHT represents the accelerating voltage, WD represents the working distance, and Mag represents the magnification.
[0026] Figure 2 This is a TEM image of the double-vacancy ZnCdS solid solution photocatalyst prepared in Example 1.
[0027] Figure 3 Hydrogen production rate graphs for the dual-vacancy ZnCdS solid solution photocatalysts prepared in Examples 1-2, the ZnCdS solid solution photocatalysts prepared in Comparative Examples 1-4, the CdS photocatalyst prepared in Comparative Example 5, the ZnS photocatalyst prepared in Comparative Example 6, and the ZnCdS solid solution photocatalyst prepared in Comparative Example 7.
[0028] Figure 4 XRD patterns of the double-vacancy ZnCdS solid solution photocatalyst prepared in Example 1, the ZnCdS solid solution photocatalysts prepared in Comparative Examples 1-4, the CdS photocatalyst prepared in Comparative Example 5, and the ZnS photocatalyst prepared in Comparative Example 6.
[0029] Figure 5 Electron paramagnetic resonance (EPR) spectra of the double-vacancy ZnCdS solid solution photocatalyst prepared in Example 1 and the ZnCdS solid solution photocatalyst prepared in Comparative Example 1.
[0030] Figure 6 The cycling curve of the double-vacancy ZnCdS solid solution photocatalyst prepared in Example 1 is shown. Detailed Implementation
[0031] The present invention will be further described below with reference to the accompanying drawings and specific preferred embodiments, but this does not limit the scope of protection of the present invention. All materials and instruments used in the following embodiments are commercially available.
[0032] Example 1
[0033] A method for preparing a dual-vacancy ZnCdS solid solution photocatalyst according to the present invention includes the following steps: (1) Add 0.06 g of cadmium acetate dihydrate, 0.54 g of zinc acetate dihydrate, and 0.18 g of thioacetamide to 60 mL of anhydrous ethanol, stir thoroughly for 10 min to dissolve until a clear solution is obtained, and place in an 80 °C constant temperature water bath for 1 h to continue the reaction. After the reaction is completed, repeat the filtration and washing 6 times, and dry the obtained solid in a 60 °C forced air drying oven for 12 h to obtain powdered ZnCdS solid solution, specifically powdered Zn 0.9 Cd 0.1 S solid solution; (2) Add 0.8g NaOH to 60mL of deionized water and stir thoroughly for 10min to dissolve, thus obtaining a NaOH solution and forming an alkaline reducing environment. Then add 0.1g of powdered Zn. 0.9 Cd 0.1 The solid solution was then subjected to ultrasonic treatment at a frequency of 40 kHz for 45 min. After ultrasonic treatment, the process of filtration and washing was repeated 6 times. The resulting solid was then dried in a forced-air drying oven at 60 °C for 12 h to obtain a double-vacancy ZnCdS solid solution photocatalyst, denoted as Zn. 0.9 Cd 0.1 S-45.
[0034] like Figure 1 As shown, the dual-vacancy ZnCdS solid solution photocatalyst Zn prepared in this embodiment... 0.9 Cd 0.1 The S-45 has a rough, uneven surface with relatively large gaps between pits, which facilitates the formation of vacancy. For example... Figure 2 As shown, Zn 0.9 Cd 0.1 Very distinct, blurry lattice fringes were observed in the irregular white areas of S-45, indirectly indicating that Zn 0.9 Cd 0.1 The S-45 has a large number of surface defects.
[0035] The hydrogen production performance of the photocatalyst was tested as follows: Weigh out 20 mg of photocatalyst (specifically Zn in this example). 0.9 Cd 0.1S-45) into a reactor containing 90 mL of deionized water, and then 10 mL of triethanolamine was added, and the reaction solution was uniformly dispersed by ultrasonic treatment for 5 min. After the Labsolar-6A online photocatalytic analysis system produced by Beijing Poliflon Technology Co., Ltd. was connected to the reactor, the system was vacuumed for half an hour to remove air in the reaction solution, 20 mL of argon was injected into the reactor for instrument protection, the plunger pump was opened to uniformly disperse argon in the system, and a magnetic stirrer was placed at the bottom of the reactor to stir the reaction solution in order to ensure the dispersibility of the photocatalyst particles as much as possible. After the plunger pump was operated for 15 min, a 300 W xenon lamp was used to irradiate from the top of the reactor to start the photocatalytic reaction. An SP-7890 gas chromatograph was used to perform online quantitative analysis on H2 generated in the reaction process, and the results are shown in Figure 3 FIG. 2. 0.9 Cd 0.1 S-45 solid solution photocatalyst reached 12.69 mmol·g -1 ·h -1 .
[0036] Example 2 A method for preparing a double-vacancy ZnCdS solid solution photocatalyst according to the present application includes the following steps: (1) 0.06 g of cadmium acetate dihydrate, 0.54 g of zinc acetate dihydrate, and 0.18 g of thioacetamide were added to 60 mL of anhydrous ethanol, and stirred to dissolve for 10 min to obtain a clear solution. The solution was placed in a 80°C constant-temperature water bath and reacted for 1 h. After the reaction was completed, the solution was repeatedly filtered and washed 6 times. The obtained solid was dried in a 60°C air-drying oven for 12 h to obtain a powder-like ZnCdS solid solution, specifically a powder-like Zn 0.9 Cd 0.1 S solid solution; (2) 0.8 g of NaOH was added to 60 mL of deionized water, and stirred to dissolve for 10 min to obtain a NaOH solution, thereby forming an alkaline reducing environment. Then, 0.1 g of the powder-like Zn 0.9 Cd 0.1 S solid solution was added, and ultrasonic treatment was performed at an ultrasonic frequency of 40 kHz for 60 min. After the ultrasonic treatment, the solution was repeatedly filtered and washed 6 times. The obtained solid was dried in a 60°C air-drying oven for 12 h to obtain a double-vacancy ZnCdS solid solution photocatalyst, which is denoted as Zn 0.9 Cd 0.1 S-60.
[0037] The hydrogen production performance test process of the photocatalyst was the same as that in Example 1. As shown in Figure 3 FIG. 3, 0.9 Cd 0.1The highest hydrogen production efficiency of the S-60 solid solution photocatalyst reaches 10.28 mmol·g -1 ·h -1 .
[0038] Comparative Example 1 A preparation method of a ZnCdS solid solution photocatalyst, comprising the following steps: 0.06 g of cadmium acetate dihydrate, 0.54 g of zinc acetate dihydrate, and 0.18 g of thioacetamide were added to 60 mL of anhydrous ethanol, and stirred to dissolve for 10 min to obtain a clear solution, which was then placed in a 80℃ constant temperature water bath for continuous reaction for 1 h. After the reaction was completed, the solid obtained was repeatedly filtered and washed 6 times, and then dried in a 60℃ air drying oven for 12 h to obtain a powder of Zn 0.9 Cd 0.1 S solid solution photocatalyst.
[0039] The hydrogen production performance test process of the photocatalyst was the same as that of Example 1, and the test results are shown in Table 1. Figure 3 The highest hydrogen production efficiency of the Zn 0.9 Cd 0.1 S solid solution photocatalyst reaches 7.01 mmol·g -1 ·h -1 .
[0040] Comparative Example 2
[0041] A preparation method of a ZnCdS solid solution photocatalyst, comprising the following steps: 0.42 g of cadmium acetate dihydrate, 0.18 g of zinc acetate dihydrate, and 0.18 g of thioacetamide were added to 60 mL of anhydrous ethanol, and stirred to dissolve for 10 min to obtain a clear solution, which was then placed in a 80℃ constant temperature water bath for continuous reaction for 1 h. After the reaction was completed, the solid obtained was repeatedly filtered and washed 6 times, and then dried in a 60℃ air drying oven for 12 h to obtain a powder of Zn 0.3 Cd 0.7 S solid solution photocatalyst.
[0042] The hydrogen production performance test process of the photocatalyst was the same as that of Example 1, and the test results are shown in Table 1. Figure 3 The highest hydrogen production efficiency of the Zn 0.3 Cd 0.7 S solid solution photocatalyst reaches 1.19 mmol·g -1 ·h -1 .
[0043] Comparative Example 3
[0044] A preparation method of a ZnCdS solid solution photocatalyst, comprising the following steps: 0.3 g of cadmium acetate dihydrate, 0.3 g of zinc acetate dihydrate, and 0.18 g of thioacetamide were added to 60 mL of anhydrous ethanol and stirred thoroughly for 10 min until a clear solution was obtained. The solution was then placed in an 80 °C water bath and reacted continuously for 1 h. After the reaction was completed, the mixture was filtered and washed 6 times. The resulting solid was dried in a 60 °C forced-air drying oven for 12 h to obtain powdered Zn. 0.5 Cd 0.5 S solid solution photocatalyst.
[0045] The testing process for the hydrogen production performance of the photocatalyst was the same as in Example 1. The test results showed that... Figure 3 As shown, Zn 0.5 Cd 0.5 The highest hydrogen production efficiency of the S solid solution photocatalyst reached 1.59 mmol·g. -1 ·h -1 .
[0046] Comparative Example 4
[0047] A method for preparing a ZnCdS solid solution photocatalyst includes the following steps: 0.18 g of cadmium acetate dihydrate, 0.42 g of zinc acetate dihydrate, and 0.18 g of thioacetamide were added to 60 mL of anhydrous ethanol and stirred thoroughly for 10 min until a clear solution was obtained. The solution was then placed in an 80 °C water bath and reacted continuously for 1 h. After the reaction was completed, the mixture was filtered and washed 6 times. The resulting solid was dried in a 60 °C forced-air drying oven for 12 h to obtain powdered Zn. 0.7 Cd 0.3 S solid solution photocatalyst.
[0048] The testing process for the hydrogen production performance of the photocatalyst was the same as in Example 1. The test results showed that... Figure 3 As shown, Zn 0.7 Cd 0.3 The highest hydrogen production efficiency of the S solid solution photocatalyst reached 2.59 mmol·g. -1 ·h -1 .
[0049] Comparative Example 5 A method for preparing a CdS photocatalyst includes the following steps: 0.6 g of cadmium acetate dihydrate and 0.18 g of thioacetamide were added to 60 mL of anhydrous ethanol and stirred thoroughly for 10 min until a clear solution was obtained. The solution was then placed in an 80 °C constant temperature water bath and reacted continuously for 1 h. After the reaction was completed, the mixture was filtered and washed 6 times. The resulting solid was dried in a 60 °C forced-air drying oven for 12 h to obtain powdered CdS photocatalyst.
[0050] The testing process for the hydrogen production performance of the photocatalyst was the same as in Example 1. The test results showed that... Figure 3As shown, the highest hydrogen production efficiency of the CdS photocatalyst reached 1.09 mmol·g -1 ·h -1 .
[0051] Comparative Example 6
[0052] A method for preparing a ZnS photocatalyst, comprising the following steps: 0.6 g of zinc acetate dihydrate, 0.18 g of thioacetamide were added to 60 mL of anhydrous ethanol, and stirred to dissolve for 10 min to a clear solution, and then placed in a 80℃ constant temperature water bath for 1 h of continuous reaction. After the reaction was completed, the solid obtained was repeatedly filtered and washed 6 times, and then dried in a 60℃ air drying oven for 12 h to obtain a powder-like ZnS photocatalyst.
[0053] The hydrogen production performance test process of the photocatalyst was the same as that of Example 1, and the test results are shown in Table 1. Figure 3 As shown, the highest hydrogen production efficiency of the ZnS photocatalyst reached 0.53 mmol·g -1 ·h -1 .
[0054] Comparative Example 7
[0055] A method for preparing a ZnCdS solid solution photocatalyst, comprising the following steps: (1) 0.06 g of cadmium acetate dihydrate, 0.54 g of zinc acetate dihydrate, and 0.18 g of thioacetamide were added to 60 mL of anhydrous ethanol, and stirred to dissolve for 10 min to a clear solution, and then placed in a 80℃ constant temperature water bath for 1 h of continuous reaction. After the reaction was completed, the solid obtained was repeatedly filtered and washed 6 times, and then dried in a 60℃ air drying oven for 12 h to obtain a powder-like Zn 0.9 Cd 0.1 S solid solution; (2) 0.1 g of the powder-like Zn 0.9 Cd 0.1 S solid solution was added to 60 mL of deionized water, and ultrasonic treatment was performed at a frequency of 40 kHz for 45 min. After ultrasonic treatment, the solid obtained was repeatedly filtered and washed 6 times, and then dried in a 60℃ air drying oven for 12 h to obtain a ZnCdS solid solution photocatalyst, which was recorded as Zn 0.9 Cd 0.1 S / N-45.
[0056] The hydrogen production performance test process of the photocatalyst was the same as that of Example 1, and the test results are shown in Table 1. Figure 3 As shown, the highest hydrogen production efficiency of the Zn 0.9 Cd 0.1 S / N-45 solid solution photocatalyst reached 7.22 mmol·g -1 ·h -1 .
[0057] Figure 4 The hydrogen production rate of the photocatalysts of Examples 1-3 and Comparative Examples 1-7 is shown in the figure. As can be seen from the figure, pure ZnS exhibits a hydrogen production rate of 0.53 mmol·g -1 ·h -1 under visible light irradiation due to its wide band gap, and pure CdS also exhibits a low hydrogen production rate of 1.09 mmol·g -1 ·h -1 For the ZnCdS solid solution photocatalyst, the hydrogen production rate gradually increases with increasing Zn 2+ ratio, and when ZnCdS is Zn 0.9 Cd 0.1 S, the hydrogen production rate reaches a maximum value of 7.01 mmol·g -1 ·h -1 The hydrogen production rate of the ZnCdS solid solution photocatalyst under different ultrasonic treatment times is higher than that of the untreated photocatalyst under the same NaOH concentration, and when the ultrasonic treatment time is 45 min, the hydrogen production rate of the ZnCdS solid solution photocatalyst can be as high as 12.69 mmol·g -1 ·h -1 which is 23.94 times that of pure ZnS and 11.64 times that of pure CdS. This is because a short ultrasonic treatment time can cause incomplete separation of vacancies and atoms, but a long ultrasonic treatment time can cause the vacancies to be saturated, and some of the overflowed atoms can return to the vacancies.
[0058] Figure 5 The XRD patterns of the photocatalysts of Examples 1-3 and Comparative Example 1-6 are shown in the figure. As can be seen from the figure, the diffraction peaks of Zn 0.9 Cd 0.1 S-45 do not shift significantly compared to Zn 0.9 Cd 0.1 S, which indicates that the Zn 0.9 Cd 0.1 S-45 treated in an alkaline environment does not undergo significant lattice changes, but the diffraction peak intensity of Zn 0.9 Cd 0.1 S-45 is slightly lower than that of Zn 0.9 Cd 0.1 S, and the peak of Zn 0.9 Cd 0.1 S-45 is broadened, which indirectly indicates the presence of vacancies.
[0059] Figure 6 The electron paramagnetic resonance (EPR) spectra of the double vacancy ZnCdS solid solution photocatalyst prepared in Example 1 and the ZnCdS solid solution photocatalyst prepared in Comparative Example 1 are shown in the figure. As can be seen from the figure, the EPR signal of the Zn 0.9 Cd0.1 S-45 with Zn 0.9 Cd 0.1 All S samples show signals at g = 2.006, which is attributed to anionic vacancies (i.e., S vacancies). If the photocatalytic material can provide extra free electrons, it will adsorb oxygen in the atmosphere and then easily accept electrons and produce vacancy signals. In theory, S vacancies can be used as electron traps to accelerate the transfer of photo-generated carriers from the bulk to the catalytic surface, prolonging the charge lifetime, while untreated Zn 0.9 Cd 0.1 S exists sulfur vacancies, which may be due to the irregular movement of molecules during synthesis, resulting in insufficient combination of S elements with Zn, Cd elements, producing a small amount of sulfur vacancies. The Zn 0.9 Cd 0.1 S-45 sample, the signal is significantly enhanced and widened, proving the increase in the concentration of sulfur vacancies (Sv) and the successful induction of defects. At the same time, for Zn 0.9 Cd 0.1 S-45 sample, two substantial paramagnetic signals attributed to S vacancies and adjacent excess cations (such as Zn 2+ ) were found at g = 2.014 and g = 2.002, respectively, which may be related to Zn vacancies. The present application uses NaOH with strong alkaline properties to establish a stable reduction environment with relatively low formation energy, thereby facilitating the formation of Zn vacancies. Ultrasonic energy produces certain physical erosion on the surface of the material, which can assist in stripping surface atoms (especially sulfur atoms), and synergize with chemical erosion to promote the formation of sulfur vacancies.
[0060] Figure 6 Cycle curve of the double vacancy ZnCdS solid solution photocatalyst prepared in Example 1. The stability of Zn 0.9 Cd 0.1 S-45 was tested, and the results are shown in It can be clearly observed that Zn 0.9 Cd 0.1 S-45 did not have a significant decrease in H2 generation in four cycles of photocatalytic reaction, thereby verifying that Zn 0.9 Cd 0.1 S-45 solid solution photocatalyst has excellent stability for photocatalytic hydrogen production. The excellent and stable photocatalytic hydrogen evolution ability can be attributed to the high charge separation efficiency and interfacial charge transfer caused by the formation of double vacancies of Zn 0.9 Cd 0.1 S-45.
[0061] The above merely describes preferred embodiments of the present application, and is not intended to limit the present application in any form. Although the present application has been disclosed with the preferred embodiments as above, it is not intended to limit the present application. Any person skilled in the art, without departing from the spirit and technical solutions of the present application, can make many possible changes and modifications to the technical solutions of the present application, or modify equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present application, without departing from the technical solutions of the present application, still belongs to the protection scope of the technical solutions of the present application.
Claims
1. A method for preparing a dual-vacancy ZnCdS solid solution photocatalyst, characterized in that, Includes the following steps: (1) Cadmium source, zinc source and sulfur source are added to anhydrous ethanol and stirred to dissolve. The mass ratio of cadmium source, zinc source and sulfur source is 1:9:3, and the mass-volume ratio of zinc source to anhydrous ethanol is 0.45g~0.54g:50mL~60mL. The reaction is carried out under water bath conditions of 70℃~90℃. After the reaction, the solution is filtered, washed and dried to obtain powdered ZnCdS solid solution, specifically powdered Zn 0.9 Cd 0.1 S solid solution; (2) Add NaOH to water and stir to dissolve. The mass-volume ratio of NaOH to water is 0.8g~0.9g∶60mL~65mL to obtain NaOH solution. Then add the powdered ZnCdS solid solution obtained in step (1) and control the mass ratio of NaOH to powdered ZnCdS solid solution to be 1∶0.1~0.
2. Then perform ultrasonic treatment. The ultrasonic frequency is 35kHz~40kHz and the ultrasonic time is 30min~60min. After ultrasonic treatment, filter, wash and dry to obtain double-vacancy ZnCdS solid solution photocatalyst.
2. The method for preparing the dual-vacancy ZnCdS solid solution photocatalyst according to claim 1, characterized in that, In step (1), the cadmium source is cadmium acetate dihydrate, the zinc source is zinc acetate dihydrate, and the sulfur source is thioacetamide.
3. The method for preparing the dual-vacancy ZnCdS solid solution photocatalyst according to claim 1, characterized in that, In step (1), the ratio of cadmium source, zinc source, sulfur source and anhydrous ethanol is 0.06g:0.54g:0.18g:60mL.
4. The method for preparing the dual-vacancy ZnCdS solid solution photocatalyst according to claim 1, characterized in that, In step (2), the mass-to-volume ratio of NaOH to water is 0.8g:60mL, the ultrasonic frequency is 40kHz, and the ultrasonic time is 45min.
5. The method for preparing a dual-vacancy ZnCdS solid solution photocatalyst according to any one of claims 1 to 4, characterized in that, In step (1), the stirring and dissolving time is 10 min to 15 min, and the reaction time is 1 h to 2 h.
6. The method for preparing a dual-vacancy ZnCdS solid solution photocatalyst according to any one of claims 1 to 4, characterized in that, In step (2), the stirring and dissolving time is 10 min to 15 min.
7. The method for preparing a dual-vacancy ZnCdS solid solution photocatalyst according to any one of claims 1 to 4, characterized in that, In step (1), the filtration and washing are repeated 3 to 6 times, and then the obtained solid is dried at a temperature of 60℃ to 65℃ for 12 to 14 hours.
8. The method for preparing a dual-vacancy ZnCdS solid solution photocatalyst according to any one of claims 1 to 4, characterized in that, In step (2), the filtration and washing are repeated 3 to 6 times, and then the obtained solid is dried at a temperature of 60℃ to 65℃ for 12 to 14 hours.
9. A dual-vacancy ZnCdS solid solution photocatalyst prepared by any one of claims 1 to 8.
10. The application of the dual-vacancy ZnCdS solid solution photocatalyst as described in claim 9 in the field of photocatalytic hydrogen production.
Citation Information
Patent Citations
Solid solution catalyst for photocatalytic decomposition of water to produce hydrogen, and preparation method thereof
CN105289656A
Preparation method of zinc sulfide cadmium solid solutions with different morphologies
CN110124692A
CdZnS nanorod photocatalytic material with surface defects as well as preparation method and application of CdZnS nanorod photocatalytic material
CN114870869A
Catalyst of titanium dioxide / zinc cadmium sulfide heterojunction hollow microspheres with zinc and oxygen double vacancies, preparation method and application
CN117427660A
Modified zinc cadmium sulfide photocatalyst as well as preparation method and application thereof
CN117531526A
Cited By
Preparation method and application of z-type heterojunction znCdS / nife LDH composite catalyst for hydrogen production by waste plastic photoreforming coupled with water decomposition
CN122352289A